Quick determination and discrimination of commercial hand sanitisers using attenuated total reflectance-Fourier transform infrared spectroscopy and chemometrics. Issue 13 (17th March 2021) - Teoh, Way Koon; Md Muslim, Noor Zuhartini; Ismail, Md Lukmi; Chang, Kah Haw; Abdullah, Ahmad Fahmi Lim
Abstract : Quick determination and discrimination of commercial hand sanitisers for forensic investigation. Abstract : Due to the outbreak of the COVID-19 pandemic, practicing personal hygiene such as frequent hand sanitising has become a norm. The making of effective hand sanitiser products should follow the recommended formulations, but the high demand worldwide for such affordable products could have made them a candidate for counterfeiting, thus deserving forensic determination and profiling for source determination or supply chain tracing. In this study, determination and discrimination of hand sanitisers was carried out by employing attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy combined with chemometrics. Fifty commercially available hand sanitisers were obtained from the market and analysed. ATR-FTIR profiles of each sanitiser were compared and decomposed by principal component analysis (PCA) followed by linear discriminant analysis (LDA). Physical observation enabled the discrimination of seven samples based on their respective colours, the presence of beads and their colours, and the physical forms of formulations. Subsequently, eight distinct patterns were observed through visual comparison of ATR-FTIR profiles of the remaining 43 samples. An initial unsupervised exploratory PCA model indicated the separation of two main groups with ATR-FTIR profiles similar to those of ethanol and isopropanol, respectively. The PCA score-LDA model provided good predictions, with a 100% correct classification into eight different groups. In conclusion, this study demonstrated a quick determination and discrimination of hand sanitiser samples, allowing screening for any restricted components and sample-to-sample comparison.